Uma aproximação do tipo Euler-Maruyama para o processo de Cox-Ingersoll-Ross - Ferreira, Ricardo Felipe (2015)
In this master's thesis we work with Cox-Ingersoll-Ross (CIR) process. This process was originally proposed by John C. Cox, Jonathan E. Ingersoll Jr. and Stephen A. Ross in 1985. Nowadays, this process is widely used in financial modeling, e.g. as a model for short-time interest rates or as volatility process in the Heston model. The stochastic diferential equation (SDE) which defines this model does not have closed form solution, so we need to approximate the process by some numerical method. In the literature, several numerical approximations has been proposed based in interval discretization. We approximate the CIR process by Euler-Maruyama-type method based in random discretization proposed by Leão e Ohashi (2013) under Feller condition. In this context, we obtain an exponential convergence order for this approximation and we use Monte Carlo techniques to compare the numerical results with theoretical values.